Phase Change Behavior and Multi-Level Storage for V2O5 Thin Film in Phase-Change Memory Application. (17th August 2020) - Xu, Yongkang; Hu, Yifeng; Sun, Song; Lai, Tianshu
Abstract : In heating process, the two obvious resistance mutations were observed for V2 O5 films at 320 °C and 345 °C. The crystallization mechanism of one-dimensional growth was the main reason for the rapid phase transition. Accompanied with the phase change, the microcrystalline and polycrystalline phases formed one after another. The element scan of micro-distribution indicated that the distribution of V and O elements were uniform. A good adhesive force was demonstrated by the scratch test. The multi-level storage was achieved in V2 O5 -based phase change memory device with a fast speed of 100 ns.